Carbon nanosphere, copper oxide and graphene oxide modified phase change microcapsule and preparation method thereof

By adding carbon nanospheres, copper oxide and graphene oxide to phase change microcapsules, the problem of insufficient thermal conductivity of existing phase change materials is solved, significantly improving the thermal conductivity and encapsulation rate of microcapsules, and improving thermal management performance .

CN119391382APending Publication Date: 2025-02-07CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411581274.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The thermal conductivity of existing phase change materials is insufficient, resulting in poor thermal energy storage performance, and the shell material of microcapsules is low, limiting the heat transfer efficiency and encapsulation rate.

Method used

By adding carbon nanospheres, copper oxide and graphene oxide to the phase change microcapsules, the modified phase change microcapsules were prepared by in-situ polymerization to form a uniform thermal conductivity and enhance the thermal conductivity of the microcapsules.

Benefits of technology

It significantly improves the thermal conductivity and encapsulation rate of phase-change microcapsules, enhances the thermal management performance of medium and high temperatures, reduces the risk of paraffin leakage, and improves the overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391382A_ABST
    Figure CN119391382A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon nanosphere, copper oxide and graphene oxide modified phase change microcapsule, and relates to the field of phase change microcapsule interface modification preparation, and the preparation method specifically comprises the following steps: A1, preparing copper oxide, A2, preparing a melamino-formaldehyde prepolymer solution, A3, preparing a microcapsule by an in-situ polymerization method, and A4, preparing the carbon nanosphere, copper oxide and graphene oxide modified phase change microcapsule. And A4, dropwise adding a melamine formaldehyde prepolymer into the reaction mixture at a rate of 2-4 ml / min, continuously stirring, adding ethylenediamine to adjust the pH value to 8-9 so as to terminate the polymerization process, neutralizing the solution, and drying in a vacuum drying oven at the temperature of 30-50 DEG C for 24 hours, thereby obtaining the microcapsule. The method has the advantages that the three different types of heat conduction reinforcing agents have excellent physical and thermal chemical properties, the phase change microcapsule is modified by mixing and hybridizing the interface, and the modified phase change material has good thermal properties and has huge potential in the aspect of medium-high temperature thermal management.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phase change materials, and in particular relates to phase change microcapsules modified by carbon nanospheres, copper oxide and graphene oxide, and a preparation method thereof. Background Art

[0002] Phase change materials have excellent thermal stability, reliability, self-cleaning ability, and efficient conversion of solar energy to thermal energy. The significant advantage is the realization of high energy storage capacity to cope with the larger latent heat of melting. The phase change temperature range is moderate, suitable for frequent use. Despite the small volume, most phase change materials have high specific heat, so thermal conductivity is an issue that needs to be addressed.

[0003] Phase change materials are classified into organic, inorganic and eutectic. Among them, organic paraffins are the most widely used and are suitable for storing solar thermal energy at low to moderate temperatures. They are chemically stable and have a large latent heat capacity. Despite its many advantages, paraffin has a significant disadvantage due to its limited thermal conductivity. Incorporating thermally conductive materials such as carbon nanotubes, graphene, and nanoparticles into the paraffin matrix, organic phase change materials show more leakage issues and result in poor thermal energy storage performance in end-use applications. Microcapsules can achieve precise temperature regulation, mitigate leakage of phase change materials, enhance thermal stability and versatility, and ensure reliability, making them an important approach in thermal energy management applications.

[0004] Inorganic shell materials have high thermal conductivity but low density. In contrast, organic materials are cheaper, easier to package, and have higher thermal stability. The development of microcapsules based on organic shells, usually polymers, is well known for its chemical and physical stability, fire resistance, and aromatic components. Melamine formaldehyde is often used as an encapsulation medium for paraffin. Microcapsules with melamine formaldehyde as shell have a smooth spherical morphology and show excellent thermal stability. The process of microencapsulating organic phase change materials with shell materials made of melamine formaldehyde through in-situ polymerization has shown improved effects in terms of encapsulation efficiency, leakage resistance, and excellent light-to-heat conversion. At the same time, microencapsulation further reduces the heat transfer of the entire material, but there are certain limitations. It reduces the heat transfer efficiency of the phase change material and the surrounding environment, and also reduces the overall performance of the encapsulated phase change material because the shell material has a low thermal conductivity. In addition, the durability of the shell material is weak, which may cause leakage of the phase change material during repeated use. At the same time, achieving higher microcapsule encapsulation efficiency remains a challenging task.

[0005] The incorporation of nanoparticles as thermal conductivity enhancers has achieved remarkable results, integrating them into microcapsules to promote uniform heat transport and thus enhance overall heat transfer. Carbon-based nanofillers with excellent thermal conductivity have excellent electrical conductivity, significant surface area, and unique chemical and thermal stability. Meanwhile, graphene has excellent mechanical properties, considerable surface area, unique physicochemical properties, and low density. Functionalized graphene nanocomposites increase the surface area and porosity and also prevent the agglomeration of graphene layers. The thermal conductivity of microcapsules can be improved by modifying the melamine formaldehyde shell with highly thermally conductive graphene oxide nanofillers.

[0006] Copper oxide is an alkaline earth metal oxide, which is widely used as a heterogeneous catalyst due to its low cost, typical physical and chemical advantages and non-corrosiveness. The high interfacial energy and sensible heat storage capacity of copper oxide are used to develop hybrid composite materials with phase change materials, and are added to phase change materials to enhance thermal conductivity. Therefore, the present invention designs carbon nanospheres, copper oxide and graphene oxide modified phase change microcapsules and preparation methods. Summary of the invention

[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0009] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing phase change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide.

[0010] In order to solve the above technical problems, the present invention provides a method for preparing phase change microcapsules modified by carbon nanospheres, copper oxide and graphene oxide, which specifically comprises the following steps:

[0011] A1. Preparation of copper oxide:

[0012] Take appropriate amount of deionized water, copper nitrate trihydrate and surfactant to dissolve, and add sodium hydroxide drops to the reaction mixture. Place the reaction mixture in a magnetic stirring water bath and stir vigorously until a highly viscous black gel is formed, and leave it overnight. Then filter, neutralize, place in a drying oven at 60℃~100℃ for drying, and calcine in a muffle furnace at 400℃~600℃ to obtain the final black powder.

[0013] A2. Preparation of melamine formaldehyde prepolymer solution:

[0014] A certain amount of deionized water is placed in a beaker, and melamine powder and formaldehyde are added thereto to obtain a melamine formaldehyde prepolymer solution. The milky white prepolymer solution is placed in a magnetic stirrer at 50°C to 70°C and stirred continuously at a speed of 50 rpm to 150 rpm until the solution becomes transparent and colorless.

[0015] A3. Preparation of microcapsules by in-situ polymerization:

[0016] Paraffin, deionized water, surfactant and sodium hydroxide powder are placed in a three-necked flask, and then the three-necked flask is placed in a magnetic stirrer at 60°C to 80°C. The paraffin is melted until a uniform emulsion is formed. The pH of the solution is maintained at an acidic pH with an acidic standard titration reagent, and dispersion solutions of carbon nanospheres, copper oxide and graphene oxide with different concentrations are added.

[0017] Then, melamine formaldehyde prepolymer is added dropwise to the reaction mixture at a rate of 2 ml / min to 4 ml / min with continuous stirring. The pH is adjusted to 8 to 9 by adding ethylenediamine to terminate the polymerization process. After the solution is neutralized, it is dried in a vacuum drying oven at 30°C to 50°C for 24 hours to obtain microcapsules.

[0018] As a preferred embodiment of the method for preparing phase change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide according to the present invention, in the steps A1 and A3, the surfactant comprises one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate or styrene maleic anhydride.

[0019] As a preferred embodiment of the method for preparing phase change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide according to the present invention, in step A3, the acidic standard titration reagent is one or more of citric acid, oxalic acid, hypochlorous acid, acetic acid, hydrofluoric acid and boric acid.

[0020] As a preferred embodiment of the method for preparing the phase change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide according to the present invention, wherein: in the step A3, the mixing stirring rate is 400 rpm to 800 rpm.

[0021] As a preferred solution of the method for preparing phase-change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide according to the present invention, wherein: in the step A3, the carbon nanospheres are 200-800 nm.

[0022] As a preferred embodiment of the method for preparing phase change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide according to the present invention, in step A3, the mixing and stirring time is 2 hours to 4 hours.

[0023] As a preferred embodiment of the method for preparing phase change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide according to the present invention, in step A3, the concentration of copper oxide during the interface modification is 0 mg / ml to 0.2 mg / ml.

[0024] As a preferred embodiment of the method for preparing phase change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide according to the present invention, the concentration of graphene oxide during the interface modification is 0 mg / ml to 1 mg / ml.

[0025] The present invention also provides a phase change microcapsule prepared by the above method, wherein the phase change material microcapsule has a stable core-shell structure, wherein the core material is an organic phase change material, the shell material is melamine formaldehyde, and the ratio of the core material to the shell material is 1:0.45.

[0026] As a preferred embodiment of the method for preparing the phase change microcapsules modified by carbon nanospheres, copper oxide and graphene oxide according to the present invention, the organic phase change material comprises one or more of paraffin, hexadecane, heptadecane, octadecane, nonadecane, eicosane, heneicosane, docosane, tricosane or tetracosane.

[0027] Beneficial effects of the present invention:

[0028] Three different types of thermal conductivity enhancers with excellent physical and thermochemical properties are used to modify phase change microcapsules through hybrid interfaces. The hybrid interface forms a uniform heat conduction channel between the core and the shell, reducing the internal heat transfer resistance. The interfacial bonding between the microcapsule particles is enhanced, and the core wax leakage is significantly reduced. The modified phase change material has good thermal properties and has great potential in medium and high temperature thermal management. Carbon nanospheres, copper oxide and graphene oxide are added to phase change microcapsules to enhance thermal conductivity. The combination of carbon-based nanoparticles and copper oxide greatly improves the thermal transfer characteristics of the material, which can be widely used in high thermal conductivity coatings, construction, textiles and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0030] Figure 1 This is a scanning electron microscope image of the modified phase change microcapsule obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0035] Example 1

[0036] Take 250ml of deionized water, dissolve 10mM copper nitrate trihydrate and 0.14g sodium dodecyl sulfate surfactant, and add 0.2M sodium hydroxide droplets to the reaction mixture. Place the reaction mixture in a magnetic stirring water bath and stir vigorously until a highly viscous black gel is formed, and leave it overnight. Then filter, neutralize, dry in a drying oven at 80℃, and calcine in a muffle furnace at 500℃ to obtain the final black powder.

[0037] 10 ml of deionized water was placed in a beaker, and 4.5 g of melamine powder and 14 ml of formaldehyde were added thereto to obtain a melamine formaldehyde prepolymer solution. The milky white prepolymer solution was placed in a magnetic stirrer at 70° C. and stirred continuously at 100 rpm until the solution became transparent and colorless.

[0038] 10g paraffin, 400mL deionized water, 3g surfactant and 1g sodium hydroxide particles were placed in a three-necked flask, and then the three-necked flask was placed in a magnetic stirrer at 70°C. After the paraffin melted, a uniform emulsion was formed. The pH of the solution was maintained at an acidic level using an acetic acid standard titration reagent, and 10mg carbon nanospheres and 0.5mg / ml graphene oxide dispersion solution were added.

[0039] Then, the melamine formaldehyde prepolymer was slowly added dropwise to the reaction mixture and stirred at 600 rpm for 3 h. The pH was adjusted to 8-9 by adding ethylenediamine to terminate the polymerization process. After the solution was neutralized, it was dried under vacuum at 40°C for 24 h to obtain microcapsules.

[0040] Example 2

[0041] The difference between this embodiment and embodiment 1 is that the concentration of graphene oxide is adjusted to 1 mg / ml, and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.

[0042] Example 3

[0043] The difference between this embodiment and embodiment 1 is that the concentration of graphene oxide is adjusted to 1.5 mg / ml, and the rest of the preparation process is the same as that of embodiment 1 to prepare microcapsules.

[0044] Example 4

[0045] Take 250ml of deionized water, dissolve 10mM copper nitrate trihydrate and 0.14g sodium dodecyl sulfate surfactant, and add 0.2M sodium hydroxide droplets to the reaction mixture. Place the reaction mixture in a magnetic stirring water bath and stir vigorously until a highly viscous black gel is formed, and leave it overnight. Then filter, neutralize, dry in a drying oven at 80℃, and calcine in a muffle furnace at 500℃ to obtain the final black powder.

[0046] 10 ml of deionized water was placed in a beaker, and 4.5 g of melamine powder and 14 ml of formaldehyde were added thereto to obtain a melamine formaldehyde prepolymer solution. The milky white prepolymer solution was placed in a magnetic stirrer at 70° C. and stirred continuously at 100 rpm until the solution became transparent and colorless.

[0047] 10g paraffin, 400mL deionized water, 3g surfactant and 1g sodium hydroxide particles were placed in a three-necked flask, and then the three-necked flask was placed in a magnetic stirrer at 70°C. After the paraffin melted, a uniform emulsion was formed. The pH of the solution was maintained at an acidic pH using an acetic acid standard titration reagent, and a dispersion solution of 10mg carbon nanospheres, 0.2mg / ml copper oxide and 1mg / ml graphene oxide was added.

[0048] Then, the melamine formaldehyde prepolymer was slowly added dropwise to the reaction mixture and stirred at 600 rpm for 3 h. The pH was adjusted to 8-9 by adding ethylenediamine to terminate the polymerization process. After the solution was neutralized, it was dried under vacuum at 40°C for 24 h to obtain microcapsules.

[0049] Example 5

[0050] The difference between this embodiment and embodiment 4 is that the concentration of copper oxide is adjusted to 0.15 mg / ml, and the rest of the preparation process is the same as that of embodiment 1 to obtain microcapsules.

[0051] Example 6

[0052] The difference between this embodiment and embodiment 4 is that the concentration of copper oxide is adjusted to 0.10 mg / ml, and the rest of the preparation process is the same as that of embodiment 1 to obtain microcapsules.

[0053] Example 7

[0054] The difference between this embodiment and embodiment 4 is that the concentration of copper oxide is adjusted to 0.05 mg / ml, and the rest of the preparation process is the same as that of embodiment 1 to obtain microcapsules.

[0055] Comparative Example 1

[0056] Take 250ml of deionized water, dissolve 10mM copper nitrate trihydrate and 0.14g sodium dodecyl sulfate surfactant, and add 0.2M sodium hydroxide droplets to the reaction mixture. Place the reaction mixture in a magnetic stirring water bath and stir vigorously until a highly viscous black gel is formed, and leave it overnight. Then filter, neutralize, dry in a drying oven at 80℃, and calcine in a muffle furnace at 500℃ to obtain the final black powder.

[0057] 10 ml of deionized water was placed in a beaker, and 4.5 g of melamine powder and 14 ml of formaldehyde were added thereto to obtain a melamine formaldehyde prepolymer solution. The milky white prepolymer solution was placed in a magnetic stirrer at 70° C. and stirred continuously at 100 rpm until the solution became transparent and colorless.

[0058] 10g paraffin, 400mL deionized water, 3g surfactant and 1g sodium hydroxide particles were placed in a three-necked flask, and then the three-necked flask was placed in a magnetic stirrer at 70°C. After the paraffin melted, a uniform emulsion was formed. The pH of the solution was maintained at an acidic level using acetic acid standard titration reagent, and 10mg carbon nanospheres were added.

[0059] Then, the melamine formaldehyde prepolymer was slowly added dropwise to the reaction mixture and stirred at 600 rpm for 3 h. The pH was adjusted to 8-9 by adding ethylenediamine to terminate the polymerization process. After the solution was neutralized, it was dried under vacuum at 40°C for 24 h to obtain microcapsules.

[0060] Comparative Example 2

[0061] The difference between this embodiment and comparative example 1 is that the weight of carbon nanospheres is adjusted to 0 g, the concentration of copper oxide added is 0.2 mg / ml, and the rest of the preparation process is the same as comparative example 1 to obtain microcapsules.

[0062] Comparative Example 3

[0063] The difference between this embodiment and comparative example 2 is that the concentration of copper oxide is adjusted to 0 mg / ml, and the rest of the preparation process is the same as that of comparative example 2 to prepare microcapsules.

[0064] Experimental Example 1

[0065] The materials obtained in the above examples and comparative examples were subjected to differential scanning calorimetry (DSC) testing, and the melting point temperature and melting latent heat value of the unmodified and modified microcapsules are shown in Table 1.

[0066] Table 1

[0067] sample Melting point temperature (℃) Latent heat of fusion (J / g) Encapsulation rate (%) paraffin 46.23 198.32 / Example 1 45.48 172.36 86.91 Example 2 43.51 174.13 87.80 Example 3 44.12 171.13 86.29 Example 4 44.76 167.39 84.40 Example 5 44.34 165.83 83.61 Example 6 44.37 159.84 80.60 Example 7 47.52 157.77 79.55 Comparative Example 1 43.76 163.51 82.45 Comparative Example 2 44.39 161.14 81.25 Comparative Example 3 34.56 162.91 82.15

[0068] When only graphene oxide is added to the microcapsule, by comparing the latent heat of melting value and encapsulation rate in the table, it can be found that Example 2 is higher than Example 1 and Example 3, so when 1 mg / ml of graphene oxide is used, the microcapsule will show good properties. The higher content of carbon nanospheres and graphene oxide in the microcapsule may lead to a reduction in the internal volume of the microcapsule, further limiting the mobility of paraffin molecules. The crystallization of paraffin is due to the fact that the movement of its molecules is restricted to a limited geometric shape, in which it is contained in a micron space due to the inclusion of carbon nanospheres, copper oxide and graphene oxide. In addition, the concentration of graphene oxide in Examples 4 to 7 is 1 mg / ml, and the encapsulation rate and melting latent heat value of the sample decrease with the reduction of copper oxide content. Compared with Examples 5 to 7 and Comparative Examples 1 to 3, the modified microcapsule of Example 4 has the highest encapsulation rate and the maximum melting latent heat value. Therefore, the addition of carbon nanospheres, copper oxide and graphene oxide can not only increase the melting latent heat value of the phase change microcapsule, but also increase the encapsulation rate of the phase change microcapsule.

[0069] Experimental Example 2

[0070] The materials obtained in the above examples and comparative examples were tested by scanning electron microscope (SEM), and the results are as follows: Figure 1 As shown. These images confirm the presence of a well-developed shell layer on the core phase change material, and all microcapsules are uniformly spherical. According to the image results, the phase change microcapsules exhibit a nearly spherical shape and are not aggregated. During the phase change process, the shell area remains unchanged and the volume of the paraffin changes. The incorporation of copper oxide and graphene oxide into the microcapsules did not affect the structure of the microcapsules, which may be due to heat dissipation caused by defects or ruptures in the microcapsule shell. The unmodified microcapsules are mainly composed of carbon, nitrogen, oxygen, aluminum and sulfur. The modified samples show the absence of aluminum, thus indicating that copper oxide is uniformly distributed on the microcapsules. In the modified phase change microcapsules, the content of carbon and oxygen elements is higher, representing graphene and higher oxygen content, respectively.

[0071] Compared with the modified microcapsules in other examples, the microcapsules prepared after modification in Example 4 have a relatively complete spherical appearance, a smooth and uniform surface, and relatively few defects and cracks in the shell.

[0072] Experiment 3

[0073] The thermal conductivity of the materials obtained in the above examples and comparative examples was tested, and the test results are shown in the following table:

[0074]

[0075]

[0076] And it can be analyzed from the table that the thermal conductivity of Example 4 is higher than that of Example 2, Comparative Example 1 and Comparative Example 2, so the addition of mixed fillers is more advantageous than the addition of single fillers. When the concentration of graphene oxide added is 1 mg / ml, as the concentration of copper oxide decreases, the thermal conductivity also decreases. Compared with paraffin and Comparative Example 3, the thermal conductivity of the modified microcapsules is improved respectively. The modified microcapsules prepared in Example 4 have a higher thermal conductivity. In the samples of Example 6 and Example 7, it is analyzed that because the outer shell has damage and holes, the defects of the shell in the microcapsules during the phase change process lead to the leakage of the core wax, and the loss of material affects the heat storage and release performance of the microcapsules. In addition, the thermal conductivity values ​​of these prepared microcapsules are also relatively low. The results show that the heat transfer efficiency of the phase change microcapsules is greatly changed by the addition of co-fillers.

[0077] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. Phase change microcapsules modified by carbon nanospheres, copper oxide and graphene oxide, characterized in that: The phase-change microcapsule has a core-shell structure including a core material and a shell material, wherein the core material is an organic phase-change material, the shell material is melamine formaldehyde, and the ratio of the core material to the shell material is 1:0.

45.

2. The phase-change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide as claimed in claim 1, characterized in that: The organic phase change material includes one or more of paraffin, hexadecane, heptadecane, octadecane, nonadecane, eicosane, heneicosane, docosane, tricosane or tetracosane.

3. The method for preparing phase-change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide according to any one of claims 1 to 2, characterized in that: The specific steps include: A1. Preparation of copper oxide: Dissolve deionized water, copper nitrate trihydrate and a surfactant, add sodium hydroxide drops to the reaction mixture, put the reaction mixture in a magnetic stirring water bath and vigorously stir until a highly viscous black gel is formed, leave it overnight, then filter, neutralize, put it in a drying oven at 60°C to 100°C for drying, and calcine it in a muffle furnace at 400°C to 600°C to obtain the final black powder; A2. Preparation of melamine formaldehyde prepolymer solution: A certain amount of deionized water is put into a beaker, and melamine powder and formaldehyde are added thereto to obtain a melamine formaldehyde prepolymer solution. The milky white prepolymer solution is put into a magnetic stirrer at 50° C. to 70° C. and stirred continuously at a speed of 50 rpm to 150 rpm until the solution becomes transparent and colorless; A3. Preparation of microcapsules by in-situ polymerization: Paraffin, deionized water, surfactant and sodium hydroxide powder are placed in a three-necked flask, and then the three-necked flask is placed in a magnetic stirrer at 60°C to 80°C. The paraffin is melted until a uniform emulsion is formed, and the pH of the solution is maintained at an acidic level with an acidic standard titration reagent, and dispersion solutions of carbon nanospheres, copper oxide and graphene oxide with different concentrations are added; A4. Add melamine formaldehyde prepolymer dropwise into the reaction mixture at a rate of 2 ml / min to 4 ml / min with continuous stirring, adjust the pH to 8 to 9 by adding ethylenediamine to terminate the polymerization process, neutralize the solution and dry it in a vacuum drying oven at 30°C to 50°C for 24 hours to obtain microcapsules.

4. The method for preparing phase-change microcapsules modified by carbon nanospheres, copper oxide and graphene oxide as claimed in claim 3, characterized in that: In the steps A1 and A3: the surfactant includes one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate or styrene maleic anhydride.

5. The method for preparing phase-change microcapsules modified by carbon nanospheres, copper oxide and graphene oxide as claimed in claim 3, characterized in that: In step A3: the acidic standard titration reagent is one or more of citric acid, oxalic acid, hypochlorous acid, acetic acid, hydrofluoric acid, and boric acid.

6. The method for preparing phase-change microcapsules modified by carbon nanospheres, copper oxide and graphene oxide as claimed in claim 3, characterized in that: In the step A3: the mixing stirring rate is 400 rpm to 800 rpm.

7. The method for preparing phase-change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide as claimed in claim 3, characterized in that: In the step A3: the carbon nanospheres are 200-800 nm.

8. The method for preparing phase-change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide as claimed in claim 3, characterized in that: In step A3: the mixing and stirring time is 2h to 4h.

9. The method for preparing phase-change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide as claimed in claim 3, characterized in that: In the step A3: the concentration of copper oxide during the interface modification is 0 mg / ml to 0.2 mg / ml.

10. The method for preparing phase-change microcapsules modified with carbon nanospheres, copper oxide and graphene oxide according to claim 3, characterized in that: In the step A3: the concentration of graphene oxide during the interface modification is 0 mg / ml to 1 mg / ml.